A CMOS current controlled ring oscillator with wide and linear tuning range. - Leelarasmee, Ekachai
A new CMOS current controlled ring oscillator is investigated. It is based on a 3 stage ring oscillator. Each stage uses a simple NMOS for switching a current source to charge a capacitor and discharging it thereby generating a ramp output. Its oscillation frequency depends on the current source. This simple circuit can have a wide tuning range but has some non-linearity problem. A modification of the original circuit using inverters can significantly improve the linearity without consuming a lot of additional current and layout. Simulation result using 1pF indicates that the oscillator has 476KHz/uA frequency sensitivity and can be tuned from 476Hz at 1nA to 476KHz at 1000nA with good linearity.
Keywords: Current controlled oscillator; Ring oscillator